In Silico Study of Curcuminoid Compounds in Turmeric ( Curcuma longa) Plants as Halal Anticoagulant Active Ingredients - Dewi, Tanaya Jati Dharma; Sya'bana, Mohammad Mohammad Ihda Faiz; Wafi, Abdul; Ma’arif, Burhan; Muchlasi, Luthfi Ahmad (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Thrombosis is a condition when there is a reduction in the flow of blood fluid in the blood vessels that occurs due to the process of forming blood clots. One of the drugs most often used as an anticoagulant is enoxaparin. Enoxaparin itself is obtained by depolymerizing the base of heparin benzyl ester which is derived directly from the intestinal mucosa of pigs so that its use triggers a lot of controversy by Muslims. The mechanism of action of enoxaparin is to act as an antithrombin III catalyst which functions to inhibit the formation of blood clots by factor X. The curcumin compound in turmeric is known to have the ability as an anticoagulant drug by inhibiting the formation of factor Xa by factor X. Objectif :This study aims to predict physicochemical properties, predict toxicity, and predict the antiviral activity of 8 curcumin-derived compounds in turmeric against antithrombin III receptors (GDP ID: 1R1L) and factor X (GDP ID: 5VOF). Methods :Prediction of physicochemical properties is carried out using the SwissADME application and referring to Lipinski's five laws . Furthermore, the toxicity class was carried out using the pkCSM Online Tool and Protox Online Tool applications. Prediction of the antiviral activity of compounds was carried out using the Molegro Virtual Docker (MVD) application.Results:The results of the LD50 value and the classification of toxicity classes were classified according to GHS. 8 compounds derived from curcumin belong to toxicity classes 4 and 5. Antithrombin III receptors (GDP ID: 1R1L) and factor X (GDP ID: 5VOF were said to be valid because they had RMSD values below 2 Å. Conclusion :The results showed that cyclocurcumin compounds were predicted to have good potential anticoagulant activity.Background: Thrombosis is a condition when there is a reduction in the flow of blood fluid in the blood vessels that occurs due to the process of forming blood clots. One of the drugs most often used as an anticoagulant is enoxaparin. Enoxaparin itself is obtained by depolymerizing the base of heparin benzyl ester which is derived directly from the intestinal mucosa of pigs so that its use triggers a lot of controversy by Muslims. The mechanism of action of enoxaparin is to act as an antithrombin III catalyst which functions to inhibit the formation of blood clots by factor X. The curcumin compound in turmeric is known to have the ability as an anticoagulant drug by inhibiting the formation of factor Xa by factor X. Objectif :This study aims to predict physicochemical properties, predict toxicity, and predict the antiviral activity of 8 curcumin-derived compounds in turmeric against antithrombin III receptors (GDP ID: 1R1L) and factor X (GDP ID: 5VOF). Methods :Prediction of physicochemical properties is carried out using the SwissADME application and referring to Lipinski's five laws . Furthermore, the toxicity class was carried out using the pkCSM Online Tool and Protox Online Tool applications. Prediction of the antiviral activity of compounds was carried out using the Molegro Virtual Docker (MVD) application.Results:The results of the LD50 value and the classification of toxicity classes were classified according to GHS. 8 compounds derived from curcumin belong to toxicity classes 4 and 5. Antithrombin III receptors (GDP ID: 1R1L) and factor X (GDP ID: 5VOF were said to be valid because they had RMSD values below 2 Å. Conclusion :The results showed that cyclocurcumin compounds were predicted to have good potential anticoagulant activity.